1201Vitamin D and family history of hypertension in relation to hypertension status among college students. (2nd September 2021) - Cuffee, Yendelela; Wang, Ming; Geyer, Nathaniel; Akuley, Susanne; Saxena, Sangeeta; Jones, Lenette; Wilson, Robin Taylor
Abstract: Background: Whereas hypertension and vitamin D concentrations have heritable components, these factors have not been investigated concurrently among young adults. The objective of this study is to investigate hypertension risk among young adults with respect to family history of hypertension, adjusting for vitamin D status. Methods: Resting blood pressure was measured in 398 college students aged 18-35 and classified according to the 2017 American Heart Association criteria. Plasma vitamin D metabolite (25(OH)D3 ; 24, 25(OH)2 D3 ; 1, 25(OH)2 D3 ) concentrations were determined using liquid chromatography tandem mass spectrometry (LC-MS/MS). Stepwise logistic regression was used to select covariates. Results: Nearly 40 percent of young adults were classified with elevated blood pressure or hypertension. Compared with no parental history, the adjusted odds ratio (AOR) for hypertension was elevated among participants with two parents having hypertension (AOR=4.5, 95% CI: 1.70-11.76), adjusting for sex, body mass index, physical activity, and plasma 25(OH)D3 . Results for systolic hypertension were similar but more extreme (two parents AOR=7.1, 95% CI: 2.82, 17.66), although dihydroxy metabolites (1, 25(OH)2 D3 and 24, 25(OH)2 D3 ) were significant. Approximately five percent (4.8%) of those with hypertension reported knowledge of their hypertensive status. Conclusions: The findings suggested a strong influence of dual parental history of hypertension on hypertensive status among young healthy adults. The overall prevalence and the combined lack of self-awareness of hypertensive status among relatively well-educated healthy young adults emphasizes the need for targeted primary and secondary prevention efforts. Key messages: Hypertension was prevalent in nearly one-third of the sample and underscores the need for targeted prevention for young adults.